2015
DOI: 10.1089/jpm.2014.0369
|View full text |Cite
|
Sign up to set email alerts
|

“Allow Natural Death” versus “Do Not Resuscitate”: What Do Patients with Advanced Cancer Choose?

Abstract: Background: Many patients with advanced cancer at our hospital request full resuscitative efforts at the end of life. We assessed the knowledge and attitudes of these patients towards end-of-life (EOL) care,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Factors associated with end‐of‐life care identified through this review are presented in Table 6 (Data S3). Patients with accurate PA were more likely to complete do‐not‐resuscitate orders (DNR), 2,3,7,51 use palliative care, 27,47,72 prefer treatment focused on comfort and quality of life, 30,34,45,57,59 and to use hospice care 30,45,57 . Patients with more accurate PA did not want to continue in life‐sustaining treatment 57 and they were not likely to be hospitalized in intensive care unit in the last year of their life 59,72 or in the last month 69 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors associated with end‐of‐life care identified through this review are presented in Table 6 (Data S3). Patients with accurate PA were more likely to complete do‐not‐resuscitate orders (DNR), 2,3,7,51 use palliative care, 27,47,72 prefer treatment focused on comfort and quality of life, 30,34,45,57,59 and to use hospice care 30,45,57 . Patients with more accurate PA did not want to continue in life‐sustaining treatment 57 and they were not likely to be hospitalized in intensive care unit in the last year of their life 59,72 or in the last month 69 .…”
Section: Resultsmentioning
confidence: 99%
“…One potential solution for this dilemma of potential negative aspects of prognostic disclosure might be in tailoring communication about prognosis according to patients' preferences rather than focus on achieving accurate prognostic awareness itself while hoping that this will ease patients' suffering. Some of the studies included in this review showed that regardless their level of quality of life or depression, patients with better prognostic awareness more often make choices which can alleviate their suffering such as preferring comfort‐oriented care, 30,59 choosing hospice care, 30,45,57 and completing DNR orders 2,3,7,51 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even aside from physical comfort, patients facing imminent death have identified that other aspects of care are equally important to their wellbeing. This includes the need for excellent culturally-appropriate communication with their health care providers that allows an understanding of their prognosis and what to expect from interventions such as resuscitation [ 12 , 13 ].…”
Section: Other Care Needs In the Final Stages Of Lifementioning
confidence: 99%
“…Clinical guidelines recommend timely ACP and palliative care as vital components of person-centered cancer care (Ferrell et al, 2017;Institute of Medicine, 2014;Levy et al, 2016;Peppercorn et al, 2011), yet most patients with cancer do not have these important conversations (Nelson et al, 2011;Peppercorn et al, 2011;Wright et al, 2008). Over half of cancer patients report that their oncologists do not know their EOL care preferences (Miljkovic, Emuron, Rhodes, Abraham, & Miller, 2015;Nelson et al, 2011). Despite ongoing efforts to increase ACP, a national longitudinal study found no increase in EOL discussions or use of living wills among persons with cancer between 2000-2012 (Narang, Wright, & Nicholas, 2015).…”
Section: Introductionmentioning
confidence: 99%